Stadium on Afternoon and its Players Behavioral Patterns of Social Interaction: Sociological Intuition Through Observation:The Case of University of Gondar - Ergano, Wondemagagn Detu (International Journal For Research In Health Sciences And Nursing, 2021)
This observational study was aimed to explore social behavioral patterns of interactions and its manifestations of football players in field at Tewodros Campus, University of Gondar. The study contained student footballers to this study in the field. The footballer’s behavioral patterns seen in field were in two continuum of dimensions. These were constructive and destructive behavioral patterns of interactions. The above two continuum of behavioral patterns had interrelation with philosophical underpinning and sociological theoretical assumptions in which were seen in field. These philosophical underpinnings give insight about how nature of social realities exists in the social spaces/football field and how these realities be understood by scholars in order to gain knowledge with following scientific research procedures and help of rigor of grammatical and logical flow of ideas in search for realities through based up on ethical principles of researches. In which, Ontological, epistemological, axiological, rhetorical, and methodological philosophical assumptions were inter-relatedly used to get sound understanding of observation as was used in the study. Also, symbolic interactionism and phenomenological theoretical assumptions were seen with the situations in the field while the researcher conducted it. Finally, this observational study was concluded with those two constructive and destructive behavioral patterns such as forming team, agreement, having nickname in field, related actions and consensus, building good emotion, and building good physical health condition and hooliganism/ interruption, verbal assaults, racism/technicism (extremism) aggressiveness and conflict respectively.